Legal Protection of Intellectual Property Rights for MSME Products in Indonesia: The Impacts of Import Relaxation Policy Under Minister of Trade Regulation No. 8 of 2024 - Alfateh, Haszmi; Azhari, Aidul Fitriciada (Journal of Law, Politic and Humanities, 2025)
This study examines the legal protection of Intellectual Property Rights (IPR) for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia amid the implementation of import relaxation under Minister of Trade Regulation No. 8 of 2024. While the policy aims to facilitate trade and material access, it raises concerns about IPR protection and MSME competitiveness. Using a qualitative case study, this research draws on interviews with MSME actors, legal experts, and officials, supported by legal documents and academic sources. Thematic analysis revealed that, although the regulation improves access to imported raw materials, it also increases IPR violations, particularly through foreign products imitating local innovations. Many MSMEs struggle to protect their intellectual assets due to weak enforcement mechanisms. The study concludes that stronger legal frameworks and government oversight are crucial to balancing trade liberalization with effective IPR safeguards. It emphasizes the need for greater awareness among MSMEs and improved institutional support to preserve local creativity and ensure fair competition. This study also proposes a collaborative policy model involving MSMEs, the government, and legal institutions to enhance sustainable IPR protection and policy coherence in the context of global trade